Analysis of the law on the prevention of money laundering and terrorism financing and law on International Sanctions and National Sanctions of the Republic of Latvia in relation to non-residents and non-entities and comparison with international requirements. Main problems and solutions - Martinova, Elena (Riga Graduate School of Law, 2019)
The study examines the impact of changes in the Law on the Prevention of Money Laundering and Terrorism Financing and Law on International Sanctions and National Sanctions of the Republic of Latvia on non-residents and non-subjects, as well as being compared with international requirements and legislation in different countries. The thesis considers what Latvian legislation is based on, whether all requirements of world and European regulators are taken into account, as well as what opportunities exist to comply with these requirements. Additionally, specific articles of Latvian legislation in anti-money laundering sphere were compared with the legislation of other countries in order to understand whether these requirements are international practice or how other countries implement the requirements of the regulator.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Money laundering; Latvia